Using Chloroquine and Hydroxychloroquine in the Treatment of COVID-19: Does It Make Sense? - Batista, Ronan (Indian Journal of Pharmaceutical Education and Research, 2020)
The severe acute respiratory syndrome caused by the new coronavirus SARS-Cov-2 (COVID-19) has quickly turned into a pandemic, infecting more than 10 million people and causing more than 500,000 deaths worldwide. The absence of an effective treatment against this disease has led several researchers to investigate the possibility of redirecting drugs already known to be effective against other diseases in the treatment of COVID-19, among them the antimalarial drugs chloroquine and hydroxychloroquine. This review aims at showing how chloroquine and hydroxychloroquine came to be considered as possible drugs in the treatment of COVID-19 and how the recent in vivo experiments described so far shed light on the adequacy of this use.
Keywords: COVID-19; SARS-Cov-2; Coronavirus; Chloroquine; Hydroxychloroquine; antiviral activity